The Effect of Higher Order Thinking Skills (HOTS) Questions on Student Writing Skills at SMA Negeri 3 Pematangsiantar - Elisabet Sinaga; Deski Ramosta Simanjuntak; Chelsi Saragih; Elsa Manurung; Basar Lolo Siahaan (PT FORMOSA CENDEKIA GLOBAL, 2023)
The objective of the research was designed to find out the students‟ ability in writing descriptive text by using HOTS questions at 8th grade in SMA Negeri 3 Pematangsiantar. It deals with content, organization, vocabulary, language use, and mechanics. The problem of this research was “to what extent does the students writing ability based on the application of HOTS questions? This research was designed as a quantitative research. The sample of this research was taken from two classes that consist of 66 students (33 students in experimental group in class 10 IPA 7 and 33 students in control group in class X IPS 1. Then quantitative data were obtained from the students‟ writing score of pre-test and post-test. The research finding of this research showed that there was an improvement on the students‟ writing ability in descriptive text based on HOTS questions. It can be seen from the mean score of pretest was 52.75 and the mean score of post-test was 80.51. And the researcher also found that t-test is higher than t-table it can be seen from df: 64 (33+33 -2) with the t-table is 1.25 and the level of significance 0.05. It shows that t-test is higher than t-table (1.27 > 1.25). After analyzing the data, the researchers concluded that using HOTS questions could develop the students‟ writing ability in descriptive text at 10th grade in SMA Negeri 3 Pematangsiantar.